Integration between science and religion analytical study on the views of Mohammad Natsir - Ishak, Mohd. Shuhaimi (s.n, 2012)
The research attempts to study the concept of Mohammad Natsir on integration between science and religion.It is also aimed at studying the purpose of education which cannot be separated from the mission of the creation of human being to undertake the task of Khilafah